Ensuring hemodialysis adequacy by dialysis dose monitoring with UV spectroscopy analysis of spent dialyzate. Issue 4 (April 2022) - Zhang, Li; Liu, Wenhu; Hao, Chuanming; He, Yani; Tao, Ye; Sun, Shiren; Jakob, Marten; Marcelli, Daniele; Barth, Claudia; Chen, Xiangmei
Introduction: Patients' session-to-session variation has been shown to influence outcomes, making critical the monitoring of dialysis dose in each session. The aim of this study was to detect the intra-patient variability of blood single pool Kt/V as measured from pre-post dialysis blood urea and from the online tool Adimea ®, which measures the ultraviolet absorbance of spent dialyzate. Methods: This open, one-armed, prospective non-interventional study, evaluates patients on bicarbonate hemodialysis or/and on hemodiafiltration. Dialysis was performed with B. Braun Dialog+ machines equipped with Adimea ® . In the course of the prospective observation, online monitoring with Adimea ® in each session was established without the target warning function being activated. A sample size of 97 patients was estimated. Results: A total of 120 patients were enrolled in six centers in China (mean age 51.5 ± 12.2 years, 86.7% males, 24.2% diabetics). All had an AV-fistula. The proportion of patients with blood Kt/V < 1.20 at baseline was 48.3%. During follow-up with Adimea ®, the subgroup with Kt/V > 1.20 at baseline remains at the same adequacy level for more than 90% of the patients. Those with a Kt/V < 1.20 at baseline, showed a significant increase of Kt/V to 60% of the patients reaching the adequacy level >1.20. The coefficient of variation for spKt/V as evaluated by Adimea ® was 9.6 ± 3.4%, not significantly different from the 9.6 ± 8.6% as blood Kt/V taken at the same time. Conclusion: Online monitoring of dialysis dose by Adimea ® improves and maintains dialysis adequacy. Implementing online monitoring by Adimea into daily practice moves the quality of dialysis patient care a significant step forward.